HUBUNGAN KREATIVITAS GURU MENGGUNAKAN MEDIA BERBASIS CANVA DENGAN HASIL BELAJAR IPA SISWA DI SEKOLAH DASAR - Handika Handika; Mery Melly Sesa; Mira Ariyanti; Mutia Rissa; Siti Fauriza; Teti Zubaida; Molly Wahyuni; Masrul Masrul (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2022)
The purpose of this study was to determine the correlation between teacher creativity in teaching variations using Canva-based media and student learning outcomes in science.The research method used is correlational quantitative. The population of this study were all fourth grade students as well as a sample of 63 students. The instruments used in this study were questionnaires and documentation. The techniques used in this research are descriptive analysis, normality test, linearity test, and hypothesis testing using the Pearson product moment test assisted by SPSS 25.The results of this study indicate that: teacher creativity in science learning has moderate criteria. Class IV science learning outcomes have a high average score with a percentage (82.3%). Based on the results of data analysis between teacher creativity and science learning outcomes there is a significant relationship with tcount 6.752 greater than ttable 2.000 or (6.752 2.000) out of n = 63 at a significant level of 5%. This shows that there is a strong, positive, and significant relationship between teacher creativity using Canva-based media and science learning outcomes for fourth grade students at SDN 006 Langgini, Bangkinang District, Kampar Regency.